Experimental investigation of thin layer drying kinetics of ghost chilli pepper (Capsicum Chinense Jacq.) dried in a forced convection solar tunnel dryer. (May 2017) - Rabha, D.K.; Muthukumar, P.; Somayaji, C.
Abstract: In this paper, a comparative study of the drying characteristic of thin layer Ghost Chilli Pepper dried in an indirect-type forced convection solar tunnel dryer and under the open sun is presented. The forced convection solar dryer consists of two double-pass solar air heaters connected in series, a semi-continuous-type tunnel dryer, a shell and tube heat exchanger, and a blower. Nine kg of the ghost chilli pepper was dried in six trays of the dryer, and a sample of 200 g was dried separately in a small tray to measure the moisture removal rate. Simultaneously, another sample of 200 g was dried under the open sun. The moisture content of the chilli samples was reduced from its initial moisture content of 589.6% (db) to the final moisture content of 12% (db) in 123 h and 193 h dried in the solar dryer and under the open sun, respectively. To select the best drying model, eleven thin layer drying models available in literature were fitted to the experimental moisture ratio data. Among these models, Page and Modified Page model for the open sun drying and Midilli and Kucuk model for the solar dryer drying were found to be suitable. Highlights: Ghost chilli dried in a forced convection solar dryer and open sun are presented. The drying process of ghost chilli occurred only in the falling rate period. Midilli and Kucuk model best describes ghost chilli drying process in solar dryer. Page and modified page model best describe ghost chilli drying process in open sun. Solar drying takes 70 h less in comparison with open sun for drying ghost chilli.